Kombinasi Metode Pembobotan Entropy dan Multi-Attribute Utility Theory Dalam Penentuan Karyawan Terbaik - Zofaisal Hamid, Pratama; Sulistiani, Heni (Universitas Muhammadiyah Jember, 2024)
Selecting the best employees is an important process in a company to recognize and reward the outstanding contributions of its employees. The main purpose of this selection is to motivate other employees to continue to improve the quality of their work, as well as create a competitive and productive work culture. The problem that arises is the potential for jealousy and unfair competition among employees in the selection process is considered not transparent or unfair, this can cause a sense of dissatisfaction and demotivation in employees who feel that their contributions are ignored. The combination of entropy and MAUT weighting methods has been an interesting approach in the context of determining the best employees. This combination provides a comprehensive and objective framework for making better decisions in selecting employees who best suit the company's needs. The ranking results provide an overview of the results of selecting the best employees using a combination of entropy and MAUT methods. Employees on behalf of Titin Yuliana were ranked 1st best employees with a final score of 0.4801, employees on behalf of Jepri were ranked 2nd best employees with a final score of 0.376, and employees on behalf of Andi were ranked 3rd best employees with a final score of 0.2929. The ranking results of the combination of entropy and MAUT methods can provide a more holistic picture of the employees who best suit the company's needs. By combining objective information about employee performance (using MAUT) with an objective evaluation of the weight of criteria (using Entropy), the end result can become more accurate and trustworthy.